2013
DOI: 10.3201/eid1902.121201
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A(H5N1) Virus Surveillance at Live Poultry Markets, Cambodia, 2011

Abstract: In Cambodia, influenza A(H5N1) virus surveillance at live poultry markets (LPMs) relies on virus isolation from poultry specimens; however, virus is rarely detected by this method. We tested 502 environmental LPM samples: 90 were positive by PCR, 10 by virus isolation. Virus circulation could be better monitored by environmental sampling of LPMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 13 publications
3
37
1
Order By: Relevance
“…Seasonal influenza A cases in humans peak in Cambodia during the rainy season, from June to December, whereas the majority of other influenza A cases (mainly H5N1) in humans and poultry occur during the mid/end of the dry season, from January to May (Mardy et al., ; Horm et al., ). The temporal peaks in H5N1 outbreaks in poultry and humans coincide with the releases of ducklings into rice fields in South Cambodia and the Chinese/Vietnamese and Cambodian New Year celebrations, when trading in livestock increases markedly (Burgos et al., ; Van Kerkhove et al., ; Sieng et al., ; Horm et al., , ). To enhance the possibility of detecting IAV, samples in this study were collected at the end of the dry season or beginning of the rainy season, in provinces exposed to repeated outbreaks of H5N1 in poultry and humans (OIE (World Health Organization For Animal Health), , World Health Organization, ,b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seasonal influenza A cases in humans peak in Cambodia during the rainy season, from June to December, whereas the majority of other influenza A cases (mainly H5N1) in humans and poultry occur during the mid/end of the dry season, from January to May (Mardy et al., ; Horm et al., ). The temporal peaks in H5N1 outbreaks in poultry and humans coincide with the releases of ducklings into rice fields in South Cambodia and the Chinese/Vietnamese and Cambodian New Year celebrations, when trading in livestock increases markedly (Burgos et al., ; Van Kerkhove et al., ; Sieng et al., ; Horm et al., , ). To enhance the possibility of detecting IAV, samples in this study were collected at the end of the dry season or beginning of the rainy season, in provinces exposed to repeated outbreaks of H5N1 in poultry and humans (OIE (World Health Organization For Animal Health), , World Health Organization, ,b).…”
Section: Discussionmentioning
confidence: 99%
“…Since 2004, Cambodia has reported 44 poultry outbreaks and 56 human cases of HP H5N1, which has led to increased active and passive influenza surveillance (World Health Organization, , OIE (World Health Organization For Animal Health, ). The active surveillance in livestock has mainly targeted detection of HP H5N1 in poultry and the surrounding environment in live bird markets (Fournié et al., ; Horm et al., , ) and serological detection of human H1N1 and H2N3 antibodies in pigs (Rith et al., ; Netrabukkana et al., ). The surveillance methods used are applicable in Cambodia since influenza vaccination is prohibited in poultry and negligible in pigs (Theary et al., ; Netrabukkana et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…267, 24 December 2012). Serum samples were collected, after obtaining informed consent, from LBM workers at the start of the study (January 2013) to form a baseline, and 8 weeks after the three major national festivals shown by previous work to be associated with increased A/H5N1 circulation in markets: 25 Lunar New Year, week 6; Khmer New Year, week 15; Pchum Ben, week 40. All adult-age LBM sellers or workers were exhaustively recruited in the four targeted livepoultry markets.…”
Section: Human Samplesmentioning
confidence: 99%
“…AIVs were detected throughout the year ( Figure 5), with a distinct peak of activity during January − March, perhaps mostly due to the increased circulation of A/H5N1 during major Cambodian festivals, as previously reported. 25 Longitudinal human serosurvey Successive serological surveys in the poultry worker cohort provided evidence of seroconversions and some prior exposure ( Table 2). At baseline sampling (January 2013), 125 participants were enrolled in the study, with one person testing positive to A/H5N1 antibodies and another testing positive to A/H9N2 antibodies.…”
Section: Animal and Environmental Surveillance Of A/h5n1mentioning
confidence: 99%
“…Recent studies, however, have shown a >2.5-fold increase in the circulation of avian H5N1 virus in live bird markets in Cambodia during 2013 compared with 2011 ( 10 , 11 ). The peak in confirmed human infections with H5N1 reassortant virus during 2013-2014 may therefore be linked to this increased circulation of H5N1 reassortant virus among poultry, but it may also reflect improved surveillance in the public health sector because our 2014 seroprevalence study does not suggest increased transmissibility of the virus to humans.…”
Section: Discussionmentioning
confidence: 98%